Determining the Effectiveness of ALMP on Youth in Serbia - Zubović, Jovan; Nikolić, Ivan (Industrija, 2013)
The focus of research in this paper is on analysing the effectiveness of the active labour market policies in one of the largest vulnerable groups in Serbian labour market - youth population. By means the nearest neighbour matched pair design applied on the youth population cohort at the labour market, the aim was to determine what policies bring about the most gains in comparison to their absence. Moreover by using PSM methodology there was performed a micro-evaluation of several different types of ALMP used in Serbia with a goal of obtaining precise information on the difference in effects among such policies. Main results show that labour market policies for youth population are at least as effective as for general population, leading to around 28% higher chance of a person participating in the treatment to remain employed 6 months later as compared to non-participants. Employment and start-up incentives and apprenticeship training show best results, but surprisingly public works have shown nearly no effects, with an expected net loss in a long term.